Correlated GNSS and temperature measurements at 10-minute intervals on the Severn Suspension Bridge - Roberts, Gethin Wyn; Brown, C.J.; Tang, X. (Springer, 2017)
Global Navigation Satellite System (GNSS) data were gathered on the 998-m-long Severn Suspension Bridge main span. The antennas were located on the tops of the four support towers, as well as five locations on the suspension cables; data were gathered at rates of 10 and 20 Hz. In addition, air and steel temperatures were gathered every 10 min. The GNSS data were processed in an On The Fly manner relative to a reference receiver located on a fixed position adjacent to the Bridge, and the resulting dataset was compared to the air and steel temperature data measurements, and correlations reported. Moving average filters that eliminate short-term movements due to wind loading and traffic loading were applied to the GNSS data, resulting in the longer-term deflections due to temperature changes every 10 min. The temperature over the 3 days varied by up to 10 °C, and movements of the order of decimetres were seen. Clear numerical correlations between the changes in temperature and the changes in height are presented when analysed at these 10-min intervals, suggesting that temperature compensation in structural health monitoring systems could be readily applied, resulting in a sustainable structure.